Otimização da secagem periódica de soja em leito fixo - Defendi, Rafael Oliveira (2015)
Brazilian production and exportation of soybean grains occupy a leading position in the global raking. One of the main expenditures related to the production of these grains is focused on the drying process. An alternative do reduce the energy consumption of this process is the intermittent drying which can lead to higher dryer performance and to enhance the mass and energy transfers. In this context, it was aimed to study the periodic operation of soybean in fixed bed focusing to find the best modulation conditions of the air temperature and its flow aiming to reduce the process energy consumption. Based on this central goal, it was established five goals related to this study: study of the air heating process with electric resistors in transient regime; drying kinetics of soybean in thin layer and mass transfer coefficient estimation; experimental and comparative study between the periodic and the conventional drying of soybean in fixed bed; modeling, validation and simulation of drying of soybean in fixed bed operating periodically and conventionally; optimization of the drying process of soybean in fixed bed with the adjusted models aiming to minimize the process energy expenditure. Results revealed that the electric heater model adjusted in transient regime showed to be ideal to estimate the necessary voltage to achieve the required temperature during the drying experiments in fixed bed according to climate conditions. In the drying kinetics studies, it was observed that the air velocity did not influence the drying kinetics, while the air temperature and the grain initial moisture content significantly impact on the drying rates. Experimental results from the soybean drying in fixed bed showed that the percentage of evaporated water was significantly higher for the periodic operation, which marked an improvement in the dryer performance for cases where both operations were conducted with the same energy consumption, air demand, climate condition and drying time. Simulating the drying process with the adjusted models, it was possible to achieve with the periodic operation a reduction of 21% in the heat input energy consumption. Optimization studies revealed that either conventional or periodic operation can be the best operational condition depending on the system initial conditions, such as the temperature and moisture content of the grain and the air. As the air and the grain characteristics vary in each industrial drying feeding, this study showed that the drying process with control strategies at the dryer entrance based on adjusted models according to the methodology used in this work can assist on the determination of the best modulation patterns of air conditions aiming to reduce the energy consumptio.